The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1007/s00261-020-02675-4
|View full text |Cite
|
Sign up to set email alerts
|

Wirsungocele: evaluation by MRCP and clinical significance

Abstract: Purpose-Wirsungocele is a rare cystic dilatation of the main pancreatic duct seen at the terminal portion of the duct of Wirsung. The purpose of our study is to evaluate the diagnostic value of MRCP in detection of Wirsungocele and the association between the MRCP-determined size of Wirsungocele and the MRCP-clinical findings of pancreatitis.Methods-Thirty-four patients with reported 'Wirsungocele' were analyzed in the study. Two radiologists reviewed MRCP/S-MRCP images for the presence and diameter of Wirsung… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…The projection images of the entire ductal system of pancreas can be achieved via endoscopic retrograde or magnetic resonance cholangiopancreatography (ERCP and MRCP). The non-invasive MRCP gives an image of lesser quality, and ERCP is thus considered to be the reference method [16]. In cases of equivocal and mild pancreatitis, the appearance of abnormal side branches is highly important for early diagnosis [17].…”
Section: Discussionmentioning
confidence: 99%
“…The projection images of the entire ductal system of pancreas can be achieved via endoscopic retrograde or magnetic resonance cholangiopancreatography (ERCP and MRCP). The non-invasive MRCP gives an image of lesser quality, and ERCP is thus considered to be the reference method [16]. In cases of equivocal and mild pancreatitis, the appearance of abnormal side branches is highly important for early diagnosis [17].…”
Section: Discussionmentioning
confidence: 99%
“…The projection images of the entire ductal system of pancreas can be achieved via endoscopic retrograde or magnetic resonance cholangiopancreatography (ERCP and MRCP). The non-invasive MRCP gives an image of lesser quality, and ERCP is thus considered to be the reference method [21]. In cases of equivocal and mild pancreatitis, the appearance of abnormal side branches is highly important for early diagnosis [22].…”
Section: Discussionmentioning
confidence: 99%
“…While Wirsungoceles are more commonly thought to be an incidental finding, a recent study suggested that Wirsungocele was significantly more likely to be present in patients with RAP than those without RAP [30]. Further evidence indicates that patients who have both pancreas divisum and a Santorinicele are at increased risk for RAP, possibly related to transient obstruction of the minor papilla [31] (FIGURE 4b).…”
Section: Why We Use Secretin Established Indications For Secretinmentioning
confidence: 99%